Pioneering biomimetic biomaterial for leukemia therapy enhancement: a review - Yao, Xiang; Wang, Zihao; Zhang, Yeke; Shao, Zhengyang; Lian, Junlan; Chen, Yue; Lin, Xuanya; Qu, Danping; Yang, Wei (Frontiers in Bioengineering and Biotechnology, 2025)
Leukemia is a highly recurrent and metastatic hematologic malignancy. The disease poses significant challenges to conventional therapies due to drug resistance, systemic toxicity, and poor drug targeting efficiency. Biomimetic biomaterials offer unique advantages for precision leukemia therapy, surpassing conventional synthetic materials in biocompatibility, biodegradability, immune evasion, and inherent targeting. These properties enable applications such as hydrogel-encapsulated systems for NK cell culture and platelet-mimetic nanocarriers for targeted drug delivery. This review first elucidates the characteristics of leukemia from microenvironmental, metabolic, and immunoregulatory perspectives. It then summarizes the design principles of biomimetic biomaterials tailored for leukemia therapy. Furthermore, the article details diverse applications of these strategies in anti-leukemic biomaterial platforms. Finally, the challenges and future opportunities for biomimetic anti-leukemia biomaterials are critically discussed across translational, technological, and interdisciplinary dimensions. By providing a comprehensive reference for researchers, this review aims to inspire innovative strategies and accelerate the development of next-generation biomaterials for leukemia treatment.